PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN KOMPETENSI GURU TERHADAP KINERJA GURU DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING DI SEKOLAH NDHOLO KUSUMO KECAMATAN TLOGOWUNGU DI KABUPATEN PATI - Mufarrida, Eny; Budiyono, Rokhmad; Novandalina, Arini (Sekolah Tinggi Ilmu Ekonomi Semarang, 2024)
Education is an important factor in efforts to improve the quality of human resources. The aim of this research is to determine and analyze the influence of principal leadership and teacher competence on teacher performance with work motivation as an intervening variable at the Ndholo Kusumo School, Tlogowungu District in Pati Regency. The population in this study were 55 teachers at the Ndholo Kusumo School, Pati Regency. The sample in this study used the census method, where all members of the population were used as samples. This research variable uses independent variables consisting of the principal's leadership and teacher competence, then teacher performance as the dependent variable and the intervening variable is work motivation which mediates the principal's leadership and teacher competence on teacher performance. The data analysis method uses path analysis. Based on the calculation results, it was obtained that the t-count value of the principal was 8.394 > t table 2.007, so the principal variable had a positive and significant effect on teacher performance, the t-count value of competency was 3.514 > t table 2.007, so the competency variable had a positive and significant effect on teacher performance and the t-count value of work motivation. is 2.843 > ttable 2.007, then the work motivation variable has a positive and significant effect on teacher performance, the t calculated value of the principal is 4.419 > t table 2.007 then the principal variable has a positive and significant effect on teacher work motivation, the calculated t value of competence is 1.058 < t table 2.007, then the competency variable has no significant effect on teacher work motivation. Path analysis shows that the indirect influence of the principal on teacher performance through work motivation is greater, namely 0.741 > 0.630, compared to the direct influence of the principal on teacher performance and the indirect influence of competence on teacher performance through work motivation is greater, namely 0.253 > 0.227, compared to the direct influence of competence. on teacher performance, so it can be concluded that work motivation is a mediating (intervening) variable between school principals and competence on teacher performance. It is best for the school principal as a leader to communicate, which is the main key for a leader to be able to know and understand his subordinates. Suggestions for the Ndholo Kusumo Foundation to improve teacher competency in the form of training and competency tests again